Integrasi Edukasi Kesehatan Berbasis Multimedia dan Produksi Kombucha Lokal untuk Pemberdayaan Masyarakat Desa Muntang - Adanti Wido Paramadini; Dasril Aldo; Faizah Faizah; Aminatus Sa'adah; Dedy Agung Prabowo; Hanief Taqiyuddien Adz-Dzaky An-Naayif; Laksmi Dwi Oktavia; Carlita Wahyu Briliana; Luciana Salsabila; Muhammad Nafal Fiqrian (Penerbit Widina, Widina Media Utama, 2025)
This community-based program aimed to improve health literacy among residents of Muntang Village, Kemangkon District, Purbalingga Regency through the integration of multimedia-based health education and the production of locally sourced kombucha as a probiotic product based on village potential. The activities were implemented through several main stages, including community needs analysis, program socialization, development and utilization of multimedia educational media, training on hygienic kombucha production using local ingredients, implementation of digital promotion, mentoring, and sustainability evaluation. The results showed a 70 percent increase in community health literacy based on pre-test and post-test comparisons involving 50 training participants. The program also successfully produced 200 bottles of local kombucha with various flavor variants and improved hygienic production skills, with all participants able to independently apply standard operating procedures. The involvement of village youth in digital promotion contributed to a 50 percent increase in social media activity within three months, while the use of digital educational media engaged 50 active users during the program period. Participant satisfaction surveys yielded an average score of 4.6 on a 5-point scale, categorized as very satisfied. Overall, the program successfully established a community empowerment model based on health literacy and local product innovation that has the potential to be sustainably replicated in other rural communities.ABSTRAKProgram pengabdian ini bertujuan untuk meningkatkan literasi kesehatan masyarakat Desa Muntang, Kecamatan Kemangkon, Kabupaten Purbalingga melalui integrasi edukasi kesehatan berbasis multimedia dan produksi kombucha lokal sebagai produk probiotik berbasis potensi desa. Kegiatan dilaksanakan melalui beberapa tahapan utama, meliputi analisis kebutuhan masyarakat, sosialisasi program, pengembangan dan pemanfaatan media edukasi multimedia, pelatihan produksi kombucha higienis berbahan lokal, penerapan promosi digital, pendampingan, serta evaluasi keberlanjutan. Hasil pelaksanaan menunjukkan peningkatan literasi kesehatan masyarakat sebesar 70 persen berdasarkan perbandingan hasil pre-test dan post-test pada 50 peserta pelatihan. Program ini juga berhasil menghasilkan 200 botol kombucha lokal dengan berbagai varian rasa, serta meningkatkan keterampilan produksi higienis masyarakat hingga seluruh peserta mampu menerapkan SOP produksi secara mandiri. Keterlibatan remaja desa dalam promosi digital berdampak pada peningkatan aktivitas media sosial sebesar 50 persen dalam tiga bulan, sementara penggunaan media edukasi digital melibatkan 50 pengguna aktif selama periode program. Survei kepuasan peserta menunjukkan skor rata-rata 4,6 pada skala 5 yang termasuk kategori sangat puas. Program ini berhasil membangun model pemberdayaan masyarakat berbasis literasi kesehatan dan inovasi produk lokal yang berpotensi direplikasi pada komunitas pedesaan lainnya secara berkelanjutan.